Optimalisasi Daya Saing Ritel Modern melalui Analisis SWOT dalam Perencanaan Strategis - Rahma, Daniar Wulan Aura; Prastiyas, David Indra; Makatita, Tegar Fajar Ramadhan; Cahyarani, Dyah Mita; Nugroho, Gwenda Vania Putri; Nugroho, Rusdi Hidayat (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
The objective is to analyze the competitiveness of modern retail through the integration of SWOT analysis as a basis for formulating more targeted strategies using qualitative descriptive methods. This paper identifies the strengths, weaknesses, opportunities, and threats that drive the performance of modern retail based on literature and empirical findings from various previous studies. The results of the analysis show that the main strengths of modern retail lie in product completeness, competitive prices, strategic locations, and operational efficiency. Meanwhile, weaknesses arise from suboptimal digitization, minimal online promotion, limited service innovation, and outdated inventory management. Meanwhile, opportunities arise from changes in digital-based shopping behavior, while threats emerge from the dominance of large retailers, e-commerce competition, and economic fluctuations. Based on the SWOT integration, a strategy is formulated that includes strengthening digitalization, optimizing online marketing, improving service quality, and modernizing operational systems to support long-term competitiveness.